2012
DOI: 10.1039/c2np90008d
|View full text |Cite
|
Sign up to set email alerts
|

Hot off the press

Abstract: A personal selection of 31 recent papers is presented covering various aspects of current developments in bioorganic chemistry and novel natural products such as hydrangenone from Salvia hydrangea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[33][34][35][36][37]79,84,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] Among these compounds, eight were new skeletons, namely, "Dysiarenone," "Septosone," "Frondoplysin," "Dysideanone," "Spiroetherane," and "Dysidavarone," and rated as "hot off the press" by Natural Product Reports. [33][34][35][36][37]97,[100][101][102][103][104] 2.2.1. Typical avarane-type SQs.…”
Section: Avarane-type Sqsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][37]79,84,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] Among these compounds, eight were new skeletons, namely, "Dysiarenone," "Septosone," "Frondoplysin," "Dysideanone," "Spiroetherane," and "Dysidavarone," and rated as "hot off the press" by Natural Product Reports. [33][34][35][36][37]97,[100][101][102][103][104] 2.2.1. Typical avarane-type SQs.…”
Section: Avarane-type Sqsmentioning
confidence: 99%
“…33–37,79,84,86–99 Among these compounds, eight were new skeletons, namely, “Dysiarenone,” “Septosone,” “Frondoplysin,” “Dysideanone,” “Spiroetherane,” and “Dysidavarone,” and rated as “hot off the press” by Natural Product Reports. 33–37,97,100–104…”
Section: Structures Classifications and Distributions Of Natural Sqsmentioning
confidence: 99%
“…2 Ent-kaurane-type diterpenoids represent one of the most excellent examples of natural products with diverse structural scaffolds and important pharmaceutical activities. 2,3 Among these compounds in our library, many unique structures, including ternifolide A, 4 neoadenoloside A, 4 neolaxiorin A, 5 nervonin A, 6 maoecrystal Z, 7 maoecrystal V, 8 xindongnin M, 9 neoangustifolin 10 and epinodosino 10 , have been reported by Natural Product Reports as hot off the press. Some compounds, such as oridonin, 11 eriocalyxin B, 12 adenanthin, 3a pharicin B, 3b and other compounds, have brought great attention to their potential antitumor application.…”
Section: Introductionmentioning
confidence: 99%
“…Fusaroside 1 is the first member of this novel class of glycolipids containing a branched lipid chain attached to the trehalose core at O-4. 2 In the preliminary studies, fusaroside showed significant growth inhibitory activity against the brine shrimp larvae 1 and is a promising compound for exploring detailed biological activity. 3 Total synthesis of fusaroside is necessary for the procurement of fusaroside and its analogues in the required amounts and purities for structure−activity relationship (SAR) studies, as well as for its structure confirmation.…”
mentioning
confidence: 99%
“…The lipid chain also has conjugated double bonds at the C-11 and C-13 positions and an isolated double bond at the C-18 position. Fusaroside 1 is the first member of this novel class of glycolipids containing a branched lipid chain attached to the trehalose core at O-4 . In the preliminary studies, fusaroside showed significant growth inhibitory activity against the brine shrimp larvae and is a promising compound for exploring detailed biological activity .…”
mentioning
confidence: 99%